2011
DOI: 10.1021/ic201671w
|View full text |Cite
|
Sign up to set email alerts
|

The Unique bis-(Disulfato)-aurate Anion [Au(S2O7)2]: Synthesis and Characterization of Li[Au(S2O7)2] and Na[Au(S2O7)2]

Abstract: The reaction of Au(OH)(3) and oleum (65% SO(3)) in the presence of M(2)SO(4) (M = Li, Na) afforded yellow single crystals of Li[Au(S(2)O(7))(2)] (triclinic, P ̅1, Z = 1, a = 532.20(3), b = 649.69(4), c = 836.72(5) pm, α = 107.982(2)°, β = 90.171(2)°, γ = 102.583(2)°, V = 267.80(3) Å(3)) and Na[Au(S(2)O(7))(2)] (monoclinic, P2(1)/n, Z = 2, a = 533.31(3), b = 1193.38(7), c = 907.67(5) pm, β = 98.548(3)°, V = 571.26(6) Å(3)). Both compounds exhibit the unprecedented [Au(S(2)O(7))(2)](-) anion in which a square pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…The B/S ratio of 1:4 still leads to a non-condensed tetrahedral moiety with a reduced charge due to the condensation of the terminal sulphate anions. This feature was recently described by Wickleder et al for complexes of transition metals like [AuA C H T U N G T R E N N U N G (S 2 O 7 ) 2 ] À [3] and [PdA C H T U N G T R E N N U N G (S 2 O 7 ) 2 ] 2À , [4] and for sulfates of Group 14 elements (Si, Ge). [5] This shows the astonishing versatility of complex sulfates.…”
Section: And Vice Versa Modifying This Pattern Li[b-supporting
confidence: 61%
See 3 more Smart Citations
“…The B/S ratio of 1:4 still leads to a non-condensed tetrahedral moiety with a reduced charge due to the condensation of the terminal sulphate anions. This feature was recently described by Wickleder et al for complexes of transition metals like [AuA C H T U N G T R E N N U N G (S 2 O 7 ) 2 ] À [3] and [PdA C H T U N G T R E N N U N G (S 2 O 7 ) 2 ] 2À , [4] and for sulfates of Group 14 elements (Si, Ge). [5] This shows the astonishing versatility of complex sulfates.…”
Section: And Vice Versa Modifying This Pattern Li[b-supporting
confidence: 61%
“…Thus, the anionic network in H 3 O[BA C H T U N G T R E N N U N G (SO 4 ) 2 ] represents an "scaled-up" variant of SiS 2 , or with regard to the H 3 O + cation, it is a filled variant of CuFeS 2 . To our knowledge, this motif is not known for silicates [15,16] but was recently found for the borophosphate Na 3 [17] and, in a more complex form, for…”
Section: Diffraction Intensities Of H[ba C H T U N G T R E N N U N G mentioning
confidence: 76%
See 2 more Smart Citations
“…Although the preparation of the acids is still tedious, we were able to prepare a couple of polysulfates, and it was found that reactions with SO 3 ‐enriched sulfuric acid (oleum) or even neat SO 3 provided access to new polysulfates with interesting properties. Among the disulfates that have to be mentioned are Re 2 O 4 Cl 2 (S 2 O 7 ) 2 , the first molecular disulfate known so far,5 Pd(S 2 O 7 ), which shows Pd 2+ in an unusual octahedral coordination, thereby leading to the magnetic behavior of the compound;6 the complex bis ‐(disulfato)‐aurate, [Au(S 2 O 7 ) 2 ] 2− ;7 and the tris ‐ and tetrakis ‐(disulfato)‐silicates [Si(S 2 O 7 ) 3 ] 2− and [Si(S 2 O 7 ) 4 ] 4− , which bear octahedral silicon coordination 8. Whereas the preparation of disulfates was quite successful, our attempts to prepare higher polysulfates led to only a limited number of polysulfates: for example, Pb(S 3 O 10 ), from the reaction of (NH 4 ) 2 [PbCl 6 ] with SO 3 ‐rich (65 %) oleum,9 and the first tetrasulfate (NO 2 ) 2 [S 4 O 13 ], which was synthesized by the reaction of SO 3 and N 2 O 5 10.…”
Section: Introductionmentioning
confidence: 99%